A comparative study on the application of different endoscopic diagnostic methods in the differential diagnosis of benign and malignant bile duct strictures - Zhu, Liang; Huang, Zhi-Quan; Wang, Zhen-Wen; Yang, Xue-Ping; Hong, Jun-Bo; Yang, Zhen-Zhen; Yu, Zheng-Ping; Cao, Rong-Lai; He, Jin-Li; Chen, You-Xiang (Frontiers in Medicine, 2023)
Objective To compare the diagnostic value of cytobrush, ERCP-guided biopsy, SpyGlass direct visual impression and SpyGlass-guided biospy (SpyBite) in the differential diagnosis of benign and malignant bile duct strictures. Methods The data of 1008 patients who were clinically diagnosed with indeterminate biliary strictures and underwent ERCP-guided biopsy, cytobrush, SpyGlass direct visual impression or SpyBite at the First Affiliated Hospital of Nanchang University between January 2010 and December 2019 were collected and analyzed retrospectively. The final diagnose was determined by surgical pathological specimen or follow-up (Malignant stricture can be identified if the stricture showed malignant progression during one year of follow-up). The differential diagnostic value of the above endoscopic diagnostic methods was evaluated by means of sensitivity, specificity, accuracy, positive predictive value, negative predictive value, etc. and safety was evaluated by the incidence rate of adverse events. Results In terms of sensitivity, standard biopsy group (48.6%) and SpyBite group (61.5%) were significantly higher than cytobrush group (32.0%), and visual impression group (100%) was significantly higher than any other group. As far as specificity was concerned, cytobrush group (99.0%), standard biopsy group (99.3%) and the SpyBite group (100%) were significantly higher than visual impression (55.6%), but there was no statistical difference among the three groups above. As far as accuracy was concerned, standard biopsy group (65.3%), and SpyBite group (80.0%) were significantly higher than cytobrush group (44.4%), and SpyBite group (80.0%) was significantly higher than visual impression group (54.8%). In terms of safety, visual impression group and SpyBite group were significantly higher than cytobrush group and standard biopsy group in post-ERCP cholangitis. Conclusion SpyBite combined with SpyGlass-guided visual impression was better for differential diagnosis of benign and malignant bile duct strictures in terms of sensitivity and accuracy compared with conventional endoscopic diagnostic methods such as cytobrush and standard biopsy. Furthmore, the incidence rates of adverse events after SpyGlass examination was similar to those after conventional endoscopic diagnostic methods except for higher cholangitis, which could be controlled by antibiotics and might be avoided by adequate biliary drainage.